نه‌خش و زه‌خره‌فه‌ی سەر كێلى‌ گۆڕەکانی گومەزى سلێمان پاشای بابان لە گردی سەیوان (شێخ مارف) - حاجى, پ.ی. د. زریان; قادر, پ.د.عەبدوڵڵا خورشيد; بەرزنجى, م. مهدى جلال مصطفى (Sulaimani Journal for Humanities, 2023)
The dome of Suleiman Pasha Babani is located in the middle of the cemetery on the mound in the middle of the cemetery called Grdi Sawan, on the hill known as Sheikh Marv al-Nudhi. This cemetery is located in the southeast of the city of Silamani, and now it is part of the city of Silemani within the locality of Sawan. It is about (3) km from the city center and the old town. This shrine is considered one of the archaeological and heritage shrines in terms of the architectural style of its dome, as well as the decorations on the seven tombstones inside this dome, where only two of them are decorated and the rest are without decorations. In this research, we shed light on the history of this shrine and the will of Suleiman Pasha to bury him here with his wife, where he died before his death. Suleiman Pasha was buried there after his death in 1846 AD. In this research, after a great effort, we were able, for the first time, to make a comprehensive study on these two tombs, trying to read the texts inscribed on the tombstones of this shrine. And to identify the texts engraved on these decorations of the tombstones, which consist of the name of the deceased and his lineage, and the date of their death, from reading Arabic texts, where they consist of Quranic verses and poetic verses in the Persian language, and the date of death, and in this research after studying the fauna decorations And the geometric patterns and inscriptions on these tombstones, we compare them with similar decorations on the tombstones of Babani and other tombstones in the region.
Keywords: dome; Suleiman Pasha; Gvrdi Sawan; tombstones; gravestone